(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. The aim of this study was to determine the incidence of acute renocardiac syndrome (cardiorenal syndrome type 3) and its outcome in a suburban population in India. Materials and Methods. In an observational study, 100 patients admitted with acute kidney injury were evaluated. Results. Acute renocardiac syndrome was documented in 29%. Acute gastroenteritis (46%) was the leading cause of acute kidney injury. Cardiogenic pulmonary edema (56%) was the most common cause of acute cardiac dysfunction. Only 42% of the patients with acute renocardiac syndrome had complete recovery of kidney function. Requirement of renal replacement therapy was found to be significantly high in patients with acute renocardiac syndrome (43% versus 9% in those with AKI and no cardiorenal syndrome) and was associated with high rate of mortality (17%). Conclusions. This study shows that the incidence of acute renocardiac syndrome is high and is associated with increased morbidity and mortality. Hence, there is a need for primordial prevention and early intervention on large scale.